Geografia e educação inclusiva: a formação docente com foco no Transtorno do Espectro Autista - TEA - Arruda, Fabrícia Íris de (2023)
In higher education courses in the country, there is still an existing gap with regard to teacher training, especially teacher training to work with autistic students. Even though some higher education courses have already included subjects on inclusive education in their grades, even so, specific training for this public is practically non-existent. The present research aims to understand the scenario of the formation of geography teachers in the context of special education, for the work of students with Autistic Spectrum Disorder (ASD), in full-time schools of the state network in the city of Campina Grande-PB, having as a criterion for selection schools that have multifunctional resource rooms. As a methodological basis, we are based on a qualitative and quantitative approach, using a bibliographic review, data surveys and reflections on the data obtained; as for its objectives, we characterized it as an exploratory research and the technical procedures adopted, a collaborative research. The field work was consolidated in seven schools and the participation of seventeen geography teachers from Escolas Cidadãs Integral and Cidadãs Integrais Técnicas. Data surveys led us to realize that the existing gaps for working with students with disabilities start from academic training and permeate to educational teaching systems. Continuing education becomes a challenge in view of the precariousness of the teacher's work, due to the lack of commitment of our rulers and the lack of respect in valuing human work, making up inclusive proposals in the 21st century is a setback in education. Thus, it is convenient to highlight the importance of continuing education for geography teachers for inclusive education focused on the learning of students with Autistic Spectrum Disorder, taking into account the increased presence of students with ASD in school spaces, for this purpose continuing training was organized in three meetings with teachers, with guidance on theories and practices in special education, with emphasis on students with ASD. Teachers' participation during training reaffirmed the lack of guidelines for work in theory and pedagogical practice with students with ASD. Among the challenges are the difficulty in adequate methodology, the lack of knowledge about the spectrum, the lack of necessary resources to work in the classroom and the absence of continuing education. As an educational product resulting from this research, a guide anchored on the bases of Universal Design for Learning was prepared, with suggestions of pedagogical practices for the construction of an inclusive work based on equity and respect for diversity.